2020
DOI: 10.1111/sdi.12909
|View full text |Cite
|
Sign up to set email alerts
|

Point‐of‐care ultrasound use for vascular access assessment and cannulation in hemodialysis: A scoping review

Abstract: Point‐of‐care ultrasound (POCUS) for access assessment and guided cannulation has become more common in hemodialysis units. The aims of this scoping review were to determine: circumstances in which renal nurses and technicians use POCUS; the barriers and facilitators; and evidence of the effects of POCUS in guiding assessment and cannulation. A search was conducted of CINAHL, Medline, Cochrane Database of Systematic Reviews, Cochrane Central Register of Controlled Trials, and ProQuest, Trove and Google Scholar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 29 publications
0
30
0
3
Order By: Relevance
“…Ultrasound guided cannulation is probably the most documented and promising method for improved cannulation. A recent systematic review found 21 relevant published studies, but only 5 were primary research publications and the number of included patients was rather low (10). They concluded that there was a lack of robust studies, but ultrasound guided cannulation could probably increase the number of successful cannulations and reduce the risk of complications and misalignment of the needles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound guided cannulation is probably the most documented and promising method for improved cannulation. A recent systematic review found 21 relevant published studies, but only 5 were primary research publications and the number of included patients was rather low (10). They concluded that there was a lack of robust studies, but ultrasound guided cannulation could probably increase the number of successful cannulations and reduce the risk of complications and misalignment of the needles.…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of studies have suggested various methods and devices to improve AVF cannulation success rates. Point-of-care ultrasound-guided cannulation has reduced the number of miscannulations (10,11), but clinical uptake has been very limited and the technique is probably less useful for buttonholes. Other suggestions include implantable metal devices to guide the cannulation of deep fistulas, plastic cannulas, and cannulation maps and skin markings of the fistula, but the efficacy is in general not well documented (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…In einer Übersichtsarbeit werden vielfältige Vorteile der POCUS-Punktion beschrieben 8 . Hervorzuheben sind die sichere Punktion der tief liegenden Shuntvene, die sichere Frühpunktion der neu angelegten AV-Fistel unter Verzicht eines ZVK oder das Erkennen von nicht geeigneten Punktionsorten, z.…”
Section: Stand Der Technik Und Erste Evidenzunclassified
“…„POCUS hat das Potenzial, die Punktionstechnik zu revolutionieren“ – diesen beeindruckenden Satz äußern Monika Schoch et al in der Zusammenfassung ihrer Übersichtsarbeit zur Nutzung von „point-of-care ultrasound“ bei der Shuntpunktion 8 .…”
unclassified
“…Other options include the use of ultrasound or marking the tract of the AVF. [29][30][31] Needle phobia or needle fear is a major barrier for patients toward home HD. 14 Peer support and observing other training patients place needles may help new patients.…”
Section: Clinical Summarymentioning
confidence: 99%